Ayurvedic perspective of Cerebral Palsy : A Review - Joshi, Kiran Vilasrao; Meena, Uganta; Kori, V K (International Research Journal of Ayurveda & Yoga, 2022)
The presentation of cerebral palsy can be global mental and physical dysfunction or isolated disturbances in gait, cognition, growth, or sensation. It is the most common childhood physical disability and affects 2 to 2.5 children per 1,000 born in the United States. Complications of cerebral palsy include spasticity and contractures; feeding difficulties; drooling; communication difficulties; osteopenia; osteoporosis; fractures; pain; and functional gastrointestinal abnormalities contributing to bowel obstruction, vomiting, and constipation. Present article aims to draw and interpret the Dosha involvement in cerebral palsy.